Evaluation of the Use of Waste Almond Shell Ash in Concrete: Mechanical and Environmental Properties - Demir, Tuba (Mdpi, 2025)
This study focuses on the use of almond shell ash (ASA) obtained from agricultural waste through the pyrolysis process in concrete production while, at the same time, presenting an environmentally sustainable design. For this purpose, ASA was obtained from the biomass energy facilities (BEF) for use in concrete mixes. A total of 25 concrete series were prepared, including 1 control series. In these series, 5%, 10%, 15% silica fume (SF), 5%, 10% metakaolin (MK), and 1%, 3%, 5%, and 7% ratios of ASA were chosen to be substituted by volume with cement. Fresh and hardened concrete tests were performed on the specimens. Experiments have shown that the use of ASA in concrete production improves concrete performance up to a certain extent. With the data obtained from the test results, performance evaluation was performed in the artificial neural network. Because of this evaluation, a mathematical model able to predict the concrete compressive strength with high accuracy was developed. To evaluate the effectiveness of the developed model, it was tested again on control specimens to confirm its accuracy and applicability. A life cycle assessment (LCA) was also performed. The aim is to make a new contribution to the literature and practical application with the method to be developed because of the study and to pioneer future studies in this field.
Keywords: almond shell ash; concrete; biomass energy; life cycle assessment; sustainability